A Few Remarks about the Dissident Movements and the Anti-Totalitarian Literature in Bulgaria - Gołek-Sepetliewa, Dorota (Poznańskie Studia Slawistyczne, 2014)
The aim of this article is to introduce a characteristic of the dissident movement and the anti-totalitarian literature in Bulgaria in the period 1944–1989. In the early‚ 90s a group of very important researchers began to focus on an accurate description of a Bulgarian dissident movement and migration literature. The results of researches in the field of history and literary studies do not give a coherent and explicit definition of dissent, dissident movement or migration dissident literature. In addiction recent works in literary studies, are not based on the various paradigms of dissent, but they create new terms and categories to describe the phenomena of cultural and literary period of the People’s Republic of Bulgaria from 1944 to 1989. The most popular are: alternative canon, anti-totalitarian literature, alternative literature, illegal literature – and in relation to dichotomies: literature of the PRB, socialist realism, socialist canon, official literature.